USABILITY APLIKASI RMS BOOKING BERBASIS WEB DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS. - Wiliani, Ninuk; Endang; Fitria; Rachmalia Feta, Neneng (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
Online booking service will make it easier for users to rent meeting rooms, so that it can be done more efficiently in time and place, Bank BRI provides online booking facilities, namely RMS booking. Use can make it easier for users, especially the board of directors who want to use the room for meetings. The purpose of this study is to identify what indicators need to be improved based on the importance of performance analysis. The identification results show that there are no attributes in quadrant I "main priority", there are 4 attributes that are in quadrant II "maintain achievement", there are 4 attributes that are in quadrant III "low priority" and there is 1 attribute that is in quadrant IV " excessive". RMSBooking.com usability improvement focuses on 2 attributes that are close to quadrant I, namely (1) Users can easily understand how to use and (5) Users can easily operate Navigation.